Improvement in Staphylococcus and Bacillus strain differentiation by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry profiling by using microwave-assisted enzymatic digestion - Balážová, Tereza; Šedo, Ondrej; Štefanić, Polonca; Mandić-Mulec, Ines; Vos, Michiel; Zdráhal, Zbyněk (Rapid communications in mass spectrometry, 2014)
RATIONALE: Distinguishing between individual bacterial strains below the species level is a challenge to matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) bacterial profiling. We propose a quick method for improving strain differentiation of two Staphylococcus and one Bacillus species. METHODS: An alternative procedure to the extraction protocol recommended by Bruker Daltonics was developed. Ethanol-sterilized cells of six S. aureus and six S. haemolyticus strains were digested by trypsin using 2-min microwave irradiation and were then analyzed. Twenty-eight strains belonging to two ecotypes of B. subtilis were subjected to the same procedure to extend the scope of the method. RESULTS: S. aureus and S. haemolyticus strains, only partially distinguishable by the standard sample preparation procedure, were subjected to microwave-assisted tryptic digestion. The repeatability of the procedure was checked in three experiments accomplished at weekly intervals. Clear distinction of the strains was achieved by cluster analysis. The differentiation of B. subtilis ecotypes was also improved significantly by the digestion method. The discriminatory power of the novel method was supported by an increase in the number of strain-specific peaks, as compared to the standard method. CONCLUSIONS: The method modulates the discriminatory power of MALDI-TOF MS profiling. The differentiation of a set of S. aureus, S. haemolyticus and B. subtilis strains was improved significantly after microwave-accelerated tryptic digestion of the cellular material.
Keywords: Microwaves; Molecular Typing; shluková analýza; Bacillus; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Staphylococcus; Trypsin; trypsin; Cluster Analysis; mikrovlny; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; molekulární typizace